PHARMACOLOGICAL TREATMENT OF OSTEOPOROSIS IN PATIENTS WITH CORONARY HEART DISEASE COMPLICATED BY CHRONIC HEART FAILURE - MARUSHCHAK, МARIYA; Krynytska, Inna (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Chronic heart failure (CHF) is a chronic multisystem disorder associated with a myriad of metabolic disturbances. Moreover, CHF may adversely affect bone metabolism and induce a severe bone loss, increasing susceptibility to fractures and osteoporosis. This study investigates the effect of combined calcium with Vitamin D3 supplement called calcemin advanceâ€ and calcitonin in the prophylaxis and treatment of osteopenia and osteoporosis in patients with coronary heart disease (CHD) complicated by CHF with the establishment of their influence on the bone mineral density (BMD). Methods: A total of 59 patients with CHD complicated by CHF. Interventions: The physical examination findings, dual-energy X-ray absorptiometry findings, and treatment results were assessed. Results: The results of the calcemin advance usage in patients with osteopenic changes showed a positive dynamics of the studied parameters, both in the lumbar spine and in the femoral bone. In patients with osteoporosis, the usage of osteoprotective therapy (calcemin advance+miacalcic) contributed to the increasing of BMD in the lumbar spine and in the femoral bone versus patients who received only combined calcium with Vitamin D3 supplement. Conclusions: Our results suggest that bone density screening could be recommended in patients with prevalent CHF. Moreover, the results of our investigation substantiate the necessity and effectiveness of osteoprotective therapy in patients with CHF with osteoporosis by calcitonin (Miacalcic), in combination with combined calcium and Vitamin D3 supplement (calcemin advance), and by only calcemin advance - in patients with CHF and osteopenia.